Child and neighborhood factors associated with pediatric injuries sustained while engaged in activities where helmet usage is recommended - Brent M. Troy; Maneesha Agarwal; Allison F. Linden; Andrew Jergel; Anthony Giarusso; Kiesha Fraser Doh (Injury Epidemiology)
Abstract Background Unintentional injuries, including traumatic brain injuries (TBI) during activities where helmet usage is recommended (AWHUR), are a leading cause of pediatric morbidity and mortality in the U.S. While advocacy and education are proven measures to address safety, community resources in a child’s neighborhood are known to have a large impact on their health. Methods We utilized the trauma registry at two pediatric trauma centers, in a major metropolitan area from 2018 to 2022, to perform a retrospective chart review and Geographical Information System (GIS) mapping on all AWHUR injuries that were included in the trauma registry. Data extracted from the trauma registry included: mechanism, demographics, insurance status, and injury characteristics. AWHUR data was then overlaid with the Childhood Opportunity Index (COI) to assess community resources in relation to injury characteristics. Results Our sample size included 1425 children throughout the 5-year time period. The most common injury mechanisms included: bicycle 34.0%, ATV 18.2%, skateboard 13.3%, scooter 9.2%, and dirt-bike 7.4%. Most patients in very low and low COI were publicly insured, respectively 81.9% and 63.2%; while 65.8% of high COI injured patients were privately insured children. There was a statistically significant difference in helmet usage across different levels of COI (p < 0.001). The rates of helmet usage by COI ranking from very low to very high were as follows: 21.6%, 25.2%, 37.8%, 40.2%, and 51.6% utilization. Among those injured while wearing a helmet, the odds of sustaining a higher ISS were 34% lower (OR = 0.66, 95% CI: 0.50—0.89) compared to those who were not wearing a helmet at the time of injury. Additionally, GIS mapping identified low and very low COI communities with higher injury rates and lower helmet use. Conclusion Children with lower COI were more likely to be publicly insured with a lower percentage of helmet usage. Overlapping injury data and COI identified high-risk communities where low resources can contribute to growing injury severity. This data can then be used to inform injury prevention and highlight the importance of community factors.